Progressive Taxation of Extractive Resources as Second-Best Optimal Policy - Wen, Jean-Francois (IMF Working Papers; Working Paper, 2018)
The paper provides a critical review of the literature on the concept of progressivity in the taxation of petroleum and mineral resources and offers a fresh perspective on its purpose and measurement. Regressive taxes, such as royalties, exist to satisfy policy objectives other than revenue maximization, such as achieving early revenues, while rent-based or profit-sensitive fiscal instruments must be designed with progressive marginal rates to maximize government revenues. Hence, the emphasis should be placed on tax rate progression of the direct taxation of profit or rent, rather than progressivity in the overall government take. However, as regressive taxes, by their very nature, tend to be distortionary, the optimal degree of progression in the rent- or profit-tax rates must take these distortions into account. The central ideas are illustrated with a simple analytical model in which a second-best optimal tax rate schedule on profit is characterized in the presence of the tax distortions caused by the regressive taxes. Some practical implications of the analysis are discussed.